Leveraging an Arts-Based Approach to Foster Engagement, Nurture Kindness, and Prevent Violence - Yok-Fong Paat; Diego Garcia Tovar; Nathan W. Myers; Max C. E. Orezzoli; Anne M. Giangiulio; Sarah L. Ruiz; Angela V. Dorado; Luis R. Torres-Hostos (Behavioral Sciences)
Drawing from the insights of community partners, this study explored the roles and benefits of arts-based approaches to foster civic learning, critical media literacy, and community engagement. It also uncovered approaches to promote kindness, prevent violence, and combat online extremism, offering insights into strategies that may enhance community engagement and create a positive impact. We presented our model framework, a detailed case study of our project, and qualitative methods incorporating 15 interviews with our community partners to capture a broad range of perspectives and experiences. Interviewees were community partners who collaborated with our project in organizing events and activities using an arts-based approach to promote kindness, awareness, and violence prevention since the inception of the project. Data were analyzed using thematic data analysis. We categorized the community partners’ responses into four key themes: (1) the inherent benefits of the arts, (2) promoting kindness and preventing violence through artistic expression, (3) teaching civic responsibility through the arts, and (4) practical strategies for collaborating with community partners. The practice implications and lessons learned were discussed.